Human Resource Management Approaches in Makassar's Business Environment - Israk, Muhammad; Rosita, Rosita; Syadiq, Fajar (Journal Development Manecos, 2025)
This study explores Human Resource Management (HRM) approaches in Makassar’s business environment, focusing on strategies, challenges, and their impact on business performance. Using a qualitative methodology, data was collected through in-depth interviews with HR professionals, business leaders, and employees across various industries. The findings reveal that HRM in Makassar prioritizes financial security and job stability over intrinsic motivation and career development, contrasting with trends observed in developed economies. While structured HRM policies contribute to increased productivity, the adoption of digital HR solutions and innovation-driven strategies remains limited. Challenges such as bureaucratic constraints, management resistance to change, and budget limitations hinder the effective implementation of HRM practices. Additionally, talent retention strategies in Makassar rely heavily on salary increases and job security rather than workplace flexibility and career advancement opportunities. The study contributes to HRM literature by addressing contextual gaps and emphasizing the need for localized HR frameworks that integrate global best practices with regional economic and cultural realities. The findings suggest that businesses in Makassar must invest in workforce development, digital HR technologies, and adaptive HR strategies to remain competitive. Future research should further explore the evolving role of HRM in emerging markets and the potential for integrating technology-driven solutions to enhance employee engagement and organizational performance.